Molecular characterization and antimicrobial potential of lactic acid bacteria isolated from the Muscovy duck gut - NGUYEN PHUONG THUY; NGUYEN THANH TUU (Society for Indonesian Biodiversity, 2025)
Abstract. Thuy NP, Tuu NT. 2025. Molecular characterization and antimicrobial potential of lactic acid bacteria isolated from the Muscovy duck gut. Biodiversitas 26: 3590-3599. The rise of antibiotic resistance in poultry necessitates sustainable alternatives like probiotics. The Muscovy duck (Cairina moschata (Linnaeus, 1758)), a vital Vietnamese agricultural breed with an uncharacterized gut microbiota, is a promising source of such beneficial bacteria. This study aimed to isolate and identify Lactic Acid Bacteria (LAB) from the gastrointestinal tract of Muscovy ducks and evaluate their in vitro antimicrobial activity against key poultry pathogens. A total of thirty LAB isolates were obtained from the crop, gizzard, small intestine, and cecum using selective media. These isolates were screened for antimicrobial activity against Escherichia coli, Salmonella sp., and Staphylococcus aureus using the agar well diffusion method. The most effective isolation was identified through 16S rRNA gene sequencing. Among the isolates, D11 demonstrated the most potent and broad-spectrum inhibition, producing inhibition zones of 1.90±0.35 cm against E. coli, 1.97±0.42 cm against Salmonella sp., and 2.30±0.35 cm against S. aureus. Molecular analysis identified isolate D11 as Companilactobacillus farciminis, with a 99.64% sequence identity to the reference strain. This is the first report of C. farciminis isolation from Muscovy ducks, expanding the known microbial biodiversity of this species. The isolate's potent antimicrobial activity positions it as a strong probiotic candidate to support sustainable and healthy duck production.